Terrorism: A Dysfunctional Quagmire Over the Concept - Akame Nnoko Remi Joel (Zien Journals, 2021)
One of the most contentious questions in international politics is the question of the definition of terrorism. Perhaps one of the better-known aphorisms is that “one man’s terrorist is another man’s liberation fighter.”1 It is not accidental that this aphorism emerged within the context of the liberation struggles in Southern Africa in which the settlers/colonial oppressors described freedom fighters as terrorists and created the impression that the liberation armies were rebels without a just cause. A definition seems controversial for reasons other than conceptual issues and problems. Because labelling actions as terrorism promotes condemnation of the actors, a definition may reflect ideological or political bias
Keywords: condemnation; contentious; international; oppressors